Emotional and spiritual quotient for sustainable education’s service quality - Mazni Saad; Norliana Ahmad Shah; Kamisah Supian; Anita Abdul Rani; Imaduddin Abidin (International Journal of Evaluation and Research in Education (IJERE), 2023)
A sustainable ecosystem of universities needs to show outstanding performance in the areas of employability, institutional social responsibility, and creative and performing arts. Thus, this study determined the influential role of emotional quotient (EQ) and spiritual quotient (SQ) on the lecturers’ excellence service quality (ESQ), which eventually led to effective classroom teaching. The data of 127 respondents were analyzed using the structural equation model with partial least square. The results confirmed that both types of quotients positively influence the lecturers’ teaching progression at the university. EQ and SQ have the encouraging power to motivate the academicians for the best service to the university through a quality learning experience. It can be concise that institutions that practice EQ and SQ values can perform better and blend a harmonious working spirit and tandem with the university’s growth. Support for sustainable development goal (SDG-4) via EQ and SQ is now required in humanizing education to ensure academicians’ competency and well-being, particularly in the aftermath of the Corona Virus Disease-19 disruption. Policymakers in the university should now capitalize the intelligence through professional initiatives. This study could have been better with a bigger sample size, but the investigation had limited access due to the university's policy on privacy.